2022
DOI: 10.1098/rsif.2021.0849
|View full text |Cite
|
Sign up to set email alerts
|

On the design of particle filters inspired by animal noses

Abstract: Passive filtering is a common strategy to reduce airborne disease transmission and particulate contaminants across scales spanning orders of magnitude. The engineering of high-performance filters with relatively low flow resistance but high virus- or particle-blocking efficiency is a non-trivial problem of paramount relevance, as evidenced in the variety of industrial filtration systems and face masks. Next-generation industrial filters and masks should retain sufficiently small droplets and aerosols while hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Recently, a novel bioinspired 3D-printed filter design with five levels of tortuous airflow channels was shown to have a low pressure drop compared to commercial masks with higher capturing efficiency of particles less than Filtration efficiencies of endonasal device tested at low (30%-38%) relative humidity under accelerated saturation, per size of challenge particles and per size of device under testing. 12 μm with >80%, however, it also exhibited lower capturing efficiency with smaller particle diameters and higher velocity of airflow (20).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a novel bioinspired 3D-printed filter design with five levels of tortuous airflow channels was shown to have a low pressure drop compared to commercial masks with higher capturing efficiency of particles less than Filtration efficiencies of endonasal device tested at low (30%-38%) relative humidity under accelerated saturation, per size of challenge particles and per size of device under testing. 12 μm with >80%, however, it also exhibited lower capturing efficiency with smaller particle diameters and higher velocity of airflow (20).…”
Section: Discussionmentioning
confidence: 95%
“…This ultrafast sterilization was achieved through the structural design of aerogels; that is, large numbers of dielectrophoretic–aerodynamic traps were constructed to manipulate, capture, and inactivate bacteria (Figure b). , The nonuniform electric fields, generated around the tips of CNTs in the cell walls (Figure f), resulted in dielectrophoresis that can directionally transport to the electrode surface for particle capture . On the other hand, inspired by the long and curved turbinates in the nasal cavity of animals which helps the capture of particles to achieve a better sense, an interconnected and tortuous hierarchical cellular architecture of METs along the air direction was constructed for highly efficient filtering. , In this regard, the serpentine pathways and induced local flow instability divert the trajectories of particles, allowing for aerodynamic entrapment and effective particle retention. Furthermore, the cell walls with a nano/microstructure of self-knotted networks can effectively intercept the collided pathogens in the airflow .…”
Section: Resultsmentioning
confidence: 99%
“…27 On the other hand, inspired by the long and curved turbinates in the nasal cavity of animals which helps the capture of particles to achieve a better sense, an interconnected and tortuous hierarchical cellular architecture of METs along the air direction was constructed for highly efficient filtering. 28,29 In this regard, the serpentine pathways and induced local flow instability divert the trajectories of particles, allowing for aerodynamic entrapment and effective particle retention. Furthermore, the cell walls with a nano/microstructure of selfknotted networks can effectively intercept the collided pathogens in the airflow.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the curvature of the nasal cavity, particles and aerosols are more likely to collect during inhalation, allowing us to smell. In particular, the highly tortuous air passage in animal noses can influence particle deposition [22] [23]. Numerical simulations have shown that the movement and deposition of particles in the nasal cavity are significantly affected by changing flow and particle size.…”
Section: Introductionmentioning
confidence: 99%